Estimation of genetic and phenotypic trends for first lactation traits in Murrah buffaloes - KURALKAR, S V; RAHEJA, K L (The Indian Journal of Animal Sciences, 2013)
The aim of study was to estimate genetic and phenotypic trends in first lactation traits, viz. age at first calving (AFC). first lactation milk yield (FLMY), first lactation length (FLL) and first calving interval (FCI) in Murrah herds maintained under 3 Uttar Pradesh Government Livestock and 4 military farms. Genetic trends were estimated from regression of weighted averages of sires’ transmitting abilities for each year on the year. Best linear unbiased prediction (BLUP) procedure was used to obtain the estimates oftransmittinglabilities of sires. The annual phenotypic trends at different farrps for AFC ranged from -3.12+-1:1.67 to 2.37+-1.91 days. Genetic trend of -1.29Â±0.64 days/year for AFe at Lucknow military dairy farm was in desirable direction and significantly different from zero. Phenotypic trends in FLMY were not different from zero at all farms except Government Livestock Farm at Mathura. Annual phenotypic (7.04Â± 1.26 days) and genetic (1.03+-1:0.38 days) trends in FLL were significantly different from zero at Government Livestock Farm, Babugarh. Genetic trends for FCI at all farms were not significantly different from zero. Estimates of genetic and phenotypic trends suggest that these farms require suitable breeding schemes for bringing genetic improvement.